Unconstrained organisations managing sustainable change : unlocking the potential of people within organisations - Hutchin, Ted (Thomas Telford, 2001)
This innovative book describes the author's investigation into the surprising fact that often the expected results do not materialise once companies have identified the way forward. Having found the constraint, developed the solution and the implementation plan, it would appear that the organisation has solved the problem, but this is often not the case.